Handbook of Cultural Heritage Analysis - D'Amico, Sebastiano; Venuti, Valentina (Springer International Publishing, 2022)
Introduction -- Large facilities and cultural heritage -- Archeometry and portable instruments -- Applied geophysics -- Monitoring of Cultural Heritage, 3D Survey, Models and GIS.-Conservation and Restoration.